Empowering Youth Through Non-Formal Education: Strategies to Overcome FOMO and Social Media Addiction in Adolescents - Gumgum Gumelar; Herdiyan Maulana; Erik Erik; Mira Ariyani; Musab Isah (Universitas Negeri Semarang, 2024)
Instagram, as a social media platform, has been associated with increased levels of FOMO due to its emphasis on sharing personal experiences and achievements. Additionally, research shows that FOMO can lead to excessive engagement with Instagram, including constantly checking for updates, obsessively scrolling through feeds, and feeling anxious or irritable when unable to access the platform. This excessive use can lead to negative consequences such as decreased productivity, poor sleep quality, and difficulty forming and maintaining relationships.This study explores the mitigative role of education against the backdrop of increasing social media addiction and Fear of Missing Out (FOMO) among adolescents in Jakarta. Employing a mixed-methods approach with quantitative surveys among 211 adolescents aged 11-24, it assesses the correlation between FOMO and addiction levels, alongside evaluating digital literacy and mental health awareness programs. Results reveal a significant positive correlation between FOMO and social media addiction, with educational interventions showing promise in fostering responsible social media use. The study emphasizes the importance of integrating digital literacy into educational curricula to equip adolescents with the necessary skills to navigate the digital landscape healthily. Its novelty lies in highlighting educational strategies within a social context as effective tools for combating the psychological impacts of social media, offering a significant contribution to the discourse on digital well-being among the youth.